Screening and selection of cultures based on techno-functional properties for ripening of cream - Gupta, Himanshu; Mandal, Surajit; Tomar, S K (Indian Journal of Dairy Science, 2019)
The aim of the present study was to screen and select diacetyl producing Lactococcus lactis culture(s) based on techno-functional properties for ripening of cream to formulate defined strain starter for preparation of ripened cream. Diacetyl production (determined by Creatine test) of 13 Lactococcus cultures from National Collection of Dairy Cultures, ICAR-NDRI, Karnal was studied in skim milk at 30ËšC for 15 h. Four potent diacetyl producing cultures, namely L. lactis NCDC 97, 127, 128, 193 were selected on this basis for further study along-with diacetyl negative L. lactis NCDC 314. Growth, acidification and diacetyl production profiles of selected cultures were evaluated in skim milk and cream (40% fat) at 30ËšC for 10 h. L. lactis NCDC 128 and 193 started diacetyl production at 6 h of fermentation in skim milk as well as in cream, which was further increased upto 8 h of fermentation. Diacetyl production in cow cream (40% fat) at 8 and 10 h of fermentation were comparable. The pH of cream and skim milk dropped from 6.2 to 4.5. Viable counts were observed to be increased by 2 log from initial count of 7 log cfu/ml. Growth, acidification and diacetyl production were higher in skim milk as compared to cream.